Arbitrary position 3D tomography for practical application in combustion diagnostics. (1st December 2022) - Sanned, David; Lindström, Johan; Roth, Adrian; Aldén, Marcus; Richter, Mattias
Abstract: This work aims to make three-dimensional (3D) tomographic techniques more flexible and accessible to in-situ measurements in practical apparatus by allowing arbitrary camera placements that benefit applications with more restrictive optical access. A highly customizable, in-house developed tomographic method is presented, applying smoothness priors through Laplacian matrices and hull constraints based on 3D space carving. The goal of this paper is to showcase a reconstruction method with full user control that can be adopted to various 3D field reconstructions. Simulations and experimental measurements of unsteady premixed CH4 /air and ethanol (C2 H5 OH) diffusion pool flames were evaluated, comparing arbitrarily placed cameras around the probed domain to the more commonly used in-plane-half-circle camera arrangement. Reconstructions reproduced expected topological field features for both flame types. Results showed slight decrease in reconstruction quality for arbitrarily placed cameras compared to in-plane-half-circle arrangement. However, at lower numbers of camera views ( N q ⩽ 6) arbitrary placement showed better results. The introduced methodology will be useful for optically limited setups in terms of handling a priori information, camera placement and 3D field evaluation.